2022
DOI: 10.1007/s41230-022-2041-y
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature oxidation behavior of a cast Ti-47.5Al-2.5V-1.0Cr-0.2Zr alloy

Abstract: TiAl alloys have the advantageous properties of high specific strength, high specific stiffness, and excellent oxidation resistance, which have been utilized for turbine blades in aircraft engines and automobile engines [1][2][3] . The blades are used in high-temperature conditions, with oxidation resistance being one of the important indices in determining its application potential. TiAl alloys can exhibit good oxidation resistance after long-term thermal exposure at 700 °C [4] . But, when the temperature exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…According to the cross-sectional How to inhibit the formation and growth of TiO 2 and promote the formation of continuous dense Al 2 O 3 is the key to improving the oxidation resistance of TiAl alloys [26]. In the TiAl alloy, because the oxidation kinetics of the Ti and Al elements to form TiO 2 and Al 2 O 3 are similar, a continuous Al 2 O 3 film cannot be formed in the air atmosphere, but TiO 2 and Al 2 O 3 are formed at the same time [27]. Since the self-diffusion coefficient of the Ti element in the TiAl alloy is much larger than that of the Al element, it is beneficial to the outer diffusion of Ti to form the outermost TiO 2 layer.…”
Section: Cross-sectional Morphology Of Oxide Scalementioning
confidence: 99%
“…According to the cross-sectional How to inhibit the formation and growth of TiO 2 and promote the formation of continuous dense Al 2 O 3 is the key to improving the oxidation resistance of TiAl alloys [26]. In the TiAl alloy, because the oxidation kinetics of the Ti and Al elements to form TiO 2 and Al 2 O 3 are similar, a continuous Al 2 O 3 film cannot be formed in the air atmosphere, but TiO 2 and Al 2 O 3 are formed at the same time [27]. Since the self-diffusion coefficient of the Ti element in the TiAl alloy is much larger than that of the Al element, it is beneficial to the outer diffusion of Ti to form the outermost TiO 2 layer.…”
Section: Cross-sectional Morphology Of Oxide Scalementioning
confidence: 99%
“…The results showed that the samples prepared by SLM had better strength and hardness. In terms of high-temperature oxidation performance, Lin [11] concluded through cyclic oxidation tests and static oxidation experiments at different temperatures that the oxidation operation at high temperatures helps to improve the elongation performance and tensile strength of GH5188. Jin et al [12][13][14] carried out research on rolling bending and rolling forming of GH5188 plates and provided theoretical guidance for related manufacturing processes by combining simulation and experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature titanium alloys are widely used in aerospace and military fields due to their excellent properties, such as low density, high specific strength, high specific stiffness and excellent high-temperature creep properties [1][2][3]. With the development of aerospace vehicles towards higher flight speeds, in addition to requiring titanium alloys with low density and high strength, they are also required to withstand higher temperatures [4,5]. At present, the maximum service temperature of titanium alloys used for a long period can reach 600 • C. Typical brands are Ti-1100, IMI834, BT36, Ti60 and Ti600 alloys [6,7].…”
Section: Introductionmentioning
confidence: 99%